Development of an energy calculator (e-Calc) software (Journal of the Nutritionist-Dieticians' Association of the Philippines, 2002)
The project aimed to develop an interactive, user-friendly computer software in a compact disc (CD) that will serve as a tool in the assessment of energy balance among Filipinos. The software is capable of assessing the nutritional status of an individual, calculating energy requirement, computing energy intake, and determining exercise and food energy equivalents to burn excess calories. It also provides nutrition tips for a healthy lifestyle. The database used in estimating the energy requirements and energy value of foods were based on local and foreign data. It contains more than a thousand popular and common food items ranging from single foods to combination or cooked foods. The quantity of food is expressed in household measures like tablespoon, cup, or glass. The software is user-friendly, and people with minimal computer literacy can easily follow the instructions. The development and availability of the energy calculator software hopes to increase awareness on the importance of energy balance in the maintenance of normal weight and promotion of good health.